2022
DOI: 10.3389/fphys.2022.863457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Frequency and Intensity on Reducing Depressive Symptoms in Older Adults With Insomnia: A Pilot Randomized Controlled Trial

Abstract: BackgroundThe effects of exercise frequency and intensity on alleviating depressive symptoms in older adults with insomnia are unclear.PurposeThe purpose of this study was to investigate the influence of different exercise frequencies and intensities on prescribed aerobic-type physical activity (i.e., 75 min of vigorous-intensity exercise or 150 min of moderate-intensity exercise weekly) for reducing depressive symptoms in older adults living with insomnia, as recommended by the WHO.DesignThis study is a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 38 Additionally, those participants who were more actively engaged in treatment, such as with exercise intervention, demonstrated greater improvements in depressive symptoms and overall functioning. 39 Furthermore, 74.03% of the participants recognised the importance of continuing the treatment for a minimum of 4–6 months even after their depressive symptoms had resolved. This outcome aligned with clinical guidelines that recommend the continuation of treatment for several months postremission to prevent relapse.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Additionally, those participants who were more actively engaged in treatment, such as with exercise intervention, demonstrated greater improvements in depressive symptoms and overall functioning. 39 Furthermore, 74.03% of the participants recognised the importance of continuing the treatment for a minimum of 4–6 months even after their depressive symptoms had resolved. This outcome aligned with clinical guidelines that recommend the continuation of treatment for several months postremission to prevent relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Data were presented as mean and standard deviation. Data were analyzed by generalized estimating equation (GEE) using group and time as main effects and baseline as a covariate ( Siu et al, 2021 ; Yu et al, 2022a ; Chin et al, 2022 ). A significant group-by-time interaction indicated that there was a significant difference in the intervention-mediated changes among groups by time.…”
Section: Methodsmentioning
confidence: 99%
“…Exercises with a higher intensity might induce higher acute neuroendocrine responses and long-term adaptations in the brain’s neural architecture than exercises with lower intensity [ 36 ]. Meaningful responses may be only visible when the exercises are conducted with a certain frequency and duration [ 37 ].…”
Section: Introductionmentioning
confidence: 99%